The Broad Spectrum of LMNA Cardiac Diseases: From Molecular Mechanisms to Clinical Phenotype - Crasto, Silvia; My, Ilaria; Di Pasquale, Elisa (Frontiers in Physiology, 2020)
Mutations of Lamin A/C gene (LMNA) cause laminopathies, a group of disorders associated with a wide spectrum of clinically distinct phenotypes, affecting different tissues and organs. Heart involvement is frequent and leads to cardiolaminopathy (LMNA-CMP), a form of dilated cardiomyopathy typically associated with conduction disorders and arrhythmias, that can manifest either as an isolated event or as part of a multisystem phenotype. Despite the recent clinical and molecular developments in the field, there is still lack of knowledge linking specific LMNA gene mutations to the distinct clinical manifestations. Indeed, the severity and progression of the disease have marked interindividual variability, even amongst members of the same family. Studies conducted so far have described Lamin A/C proteins involved in diverse biological processes, that span from a structural role in the nucleus to the regulation of response to mechanical stress and gene expression, proposing various mechanistic hypotheses. However, none of those is per se able to fully justify functional and clinical phenotypes of LMNA-CMP; therefore, the role of Lamin A/C in cardiac pathophysiology still represents an open question. In this review we provide an update on the state-of-the-art studies on cardiolaminopathy, in the attempt to draw a line connecting molecular mechanisms to clinical manifestations. While investigators in this field still wonder about a clear genotype/phenotype correlation in LMNA-CMP, our intent here is to recapitulate common mechanistic hypotheses that link different mutations to similar clinical presentations.